Food as a Cultural Text: An Analysis of Gastrocriticism on the Clean Tradition of Javanese Villages: A Literature Review - Addy Septyawan; Dwi Rohman Soleh; Diana Romdhoningsih; Rudi Karma; Nurlaily Khoirun Ni’mah; Chafit Ulya (Journal of Science and Education (JSE), 2026)
This research aims to examine food as a cultural text in the Javanese Village Clean tradition through the perspective of gastrocriticism with a Systematic Literature Review (SLR) approach. A total of 25 selected articles were analyzed using the PRISMA flow to explore how food functions as a symbol, a medium of communication, and a representation of cultural identity in the context of Javanese rituals. The results of the study show that ritual foods such as tumpeng, jenang, and offerings have a construction of meaning related to Javanese cosmology, social solidarity, and community value structure. An analysis of the cultural theories of Barthes, Douglas, and Lévi-Strauss reveals that food is not only an object of consumption, but also a system of signs that negotiates man's relationship with nature, ancestors, and communities. Most previous studies have focused on symbolic or ethnographic aspects, while this study found gaps in the integration of culinary discourse analysis with the dynamics of modernity. These findings confirm the need for a multidisciplinary approach to reading food as a cultural text, while also opening up space for further research on the transformation of traditional culinary meanings in contemporary social change. Thus, this study makes a conceptual and methodological contribution to the development of culinary cultural studies, especially in the context of Javanese rituals.